Improved cash flow and reduced operating expenses through construction change management software integration - Phillips, Dustin R. (University of Wisconsin--Stout, 2018)
The effects of change order management can be felt across all aspects of a construction project. The project duration, labor productivity, material procurement and safety are impacted based on how change orders are handled on a given project. While project management systems have enhanced communication between owners, designers and contractors, the use of these tools on the change management process has lacked efficiency. This study compares new systems against traditional methods of handling this process to analyze where efficiencies can be gained.
Keywords: Construction industry; Project management; Software